68.9% Efficient GaAs‐Based Photonic Power Conversion Enabled by Photon Recycling and Optical Resonance. Issue 7 (4th May 2021) - Helmers, Henning; Lopez, Esther; Höhn, Oliver; Lackner, David; Schön, Jonas; Schauerte, Meike; Schachtner, Michael; Dimroth, Frank; Bett, Andreas W.
Abstract : For solar cells operating under the broad‐band solar spectrum, the photovoltaic conversion efficiency is fundamentally limited by transmission and thermalization losses. For monochromatic light, these losses can be minimized by matching the photon energy and the absorber material's bandgap energy. Furthermore, for high‐crystal‐quality direct semiconductors, radiative recombination dominates the minority carrier recombination. Light‐trapping schemes can leverage reabsorption of thereby internally generated photons. Such photon recycling increases the effective excess carrier concentration, which, in turn, increases photovoltage and consequently conversion efficiency. Herein, a back surface reflector underneath a GaAs/AlGaAs rear‐heterojunction structure leverages photon recycling to effectively reduce radiative recombination losses and therefore boost the photovoltage. At the same time, resonance in the created optical cavity is tailored to enhance near‐bandgap absorption and, thus, minimize thermalization loss. With a thin film process and a combined dielectric–metal reflector, an unprecedented photovoltaic conversion efficiency of 68.9 ± 2.8% under 858 nm monochromatic light at an irradiance of 11.4 W cm −2 is demonstrated. Abstract : A thin film GaAs/AlGaAs rear‐heterojunction photonic power converter with a back reflector is presented. Photon recycling is leveraged to increase the excess carrier density and consequently the output voltage. Optical resonance yields highest absorptance for near‐bandgap photons. Thereby thermalization losses are minimized without compromising minimal transmission. A photovoltaic conversion efficiency of 68.9% for 858 nm monochromatic light is demonstrated.